The modern skeptical challenge reflected in the Private Language argument: a retelling of Saul Kripke's reading of Wittgenstein’s Philosophical Investigations - Vollet, Lucas Ribeiro (Voluntas: Revista Internacional de Filosofia, 2021)
In the following paper we explore Kripke's reading of the private language argument. Our reading affirms that line of thought: the skeptical paradox about rules that Kripke believed to have traced in this argument connects with the old skeptical question of modernity (David Hume), and gives Wittgenstein's work a reflective detachment to think about the conditions under which a semantic enigma may be resolved. We will argue that the answer involves a pragmatic shift that ends for good Wittgenstein’s intimate links with the problem of “proposition” and substitute it by another. Our view is that Wittgenstein’s reflection on language game propose a pragmatic substitute for “propositions” to protect rule-consistency in meaning and truth-prediction. The reflective course of the article will go through Gilbert Ryle's philosophy of language and his concept of category-mistakes. We finish showing solidarity with Robert Brandon’s interpretation of Wittgenstein.